PENGARUH WORK LIFE BALANCE, SELF EFFICACY, JOB SATISFACTION TERHADAP LOYALITAS KERJA KARYAWAN PADA PT BANK NEGARA INDONESIA TBK KANTOR CABANG PONOROGO - Pradestin, Isna; MM, Dr. Sri Hartono,; MM, Naning Kristiyana, SE, (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: E$mploye$e$s who have$ a high le$ve$l of loyalty are$ crucial for maintaining the$ stability and growth of the$ company. Amidst the$ de$mands of work, achie$ving a balance$ be$twe$e$n work re$sponsibilitie$s and pe$rsonal life$ be$come$s challe$nging. This study aims to analyze$ the$ e$ffe$cts of work-life$ balance$, se$lf-e$fficacy, and job satisfaction on e$mploye$e$ work loyalty at PT Bank Ne$gara Indone$sia Tbk Ponorogo Branch Office$ using multiple$ line$ar re$gre$ssion analysis. The$ re$sults of the$ study indicate$ that work-life$ balance$, se$lf-e$fficacy, and job satisfaction individually affe$ct work loyalty. Furthe$rmore$, colle$ctive$ly, work-life$ balance$, se$lf-e$fficacy, and job satisfaction have$ a significant impact on work loyalty. Keywords: Work life$ balance$, se$lf e$fficacy, job satisfaction, work loyalty. Abstrak: Karyawan yang me$miliki tingkat loyalitas tinggi sangat pe$nting untuk me$njaga stabilitas dan pe$rtumbuhan pe$rusahaan. Di te$ngah tuntutan ke$rja dalam me$njaga ke$se$imbangan antara tanggung jawab pe$ke$rjaan dan ke$hidupan pribadi me$njadi tantangan. Pe$ne$litian ini be$rtujuan me$nganalisis pe$ngaruh Work life$ balance$, Se$lf E$fficacy, dan Job Satisfaction te$rhadap loyalitas ke$rja karyawan pada PT Bank Ne$gara Indone$sia Tbk Kantor Cabang Ponorogo de$ngan me$tode$ uji analisis re$gre$si linie$r be$rganda. Hasil pe$ne$litian dite$mukan work life$ balance$ be$rpe$ngaruh te$rhadap loyalitas ke$rja, se$lf e$fficacy be$rpe$ngaruh te$rhadap loyalitas ke$rja, job satisfaction be$rpe$ngaruh te$rhadap loyalitas ke$rja, dan work life$ balance$, se$lf e$fficacy, dan job satisfaction se$cara simultan be$rpe$ngaruh te$rhadap loyalitas ke$rja. Kata kunci: Work life$ balance$, se$lf e$fficacy, job satisfaction, loyalitas ke$rja.